2017
DOI: 10.1016/j.molmet.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Repletion of branched chain amino acids reverses mTORC1 signaling but not improved metabolism during dietary protein dilution

Abstract: ObjectiveDietary protein dilution (PD) has been associated with metabolic advantages such as improved glucose homeostasis and increased energy expenditure. This phenotype involves liver-induced release of FGF21 in response to amino acid insufficiency; however, it has remained unclear whether dietary dilution of specific amino acids (AAs) is also required. Circulating branched chain amino acids (BCAAs) are sensitive to protein intake, elevated in the serum of obese humans and mice and thought to promote insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 50 publications
8
54
0
Order By: Relevance
“…Lastly, as we have previously shown that dietary protein or AA dilution can retard the development of obesity-related metabolic dysfunction, we then tested whether selective Thr restriction (LT), without total AA restriction or altered dietary carbohydrate supply, can mimic these effects in a mouse model of obesity-related metabolic dysfunction, the New Zealand Obese (NZO) mouse. Of note, similar to our prior findings of NZO mice subjected to dietary protein/AA dilution 14,49 , there was no effects of LT on body mass development and liver and adipose tissue weights (Suppl. Fig.…”
Section: Results (2422 Words)supporting
confidence: 89%
See 4 more Smart Citations
“…Lastly, as we have previously shown that dietary protein or AA dilution can retard the development of obesity-related metabolic dysfunction, we then tested whether selective Thr restriction (LT), without total AA restriction or altered dietary carbohydrate supply, can mimic these effects in a mouse model of obesity-related metabolic dysfunction, the New Zealand Obese (NZO) mouse. Of note, similar to our prior findings of NZO mice subjected to dietary protein/AA dilution 14,49 , there was no effects of LT on body mass development and liver and adipose tissue weights (Suppl. Fig.…”
Section: Results (2422 Words)supporting
confidence: 89%
“…We previously demonstrated that dietary protein dilution (DPD) improves glucose and lipid homeostasis in obesity and that dilution of amino acids was sufficient to mimic these effects 14,16,49 . However, it remained to be resolved whether the dilution of protein by substituting with other dietary nutrients (i.e.…”
Section: Results (2422 Words)mentioning
confidence: 99%
See 3 more Smart Citations